Pathogen-inspired engineering of plant protease enhances late blight resistance - Jie Huang; Alice Penrose; Laura Ossorio Carballo; Renier A. L. van der Hoorn (Proceedings of the National Academy of Sciences, 2026)
The apoplast is an important battlefield in plant–pathogen interactions. The late blight oomycete pathogen Phytophthora infestans, for instance, secretes cystatin-like protease inhibitors EpiC1 and EpiC2B to suppress C14, a papain-like immune protease secreted by tomato. Here, we found that P. infestans also secretes two distinct papain-like proteases termed Pain1 and Pain2, which are transcriptionally induced during infection. Both Pains promote P. infestans infection, but not when their catalytic residues are mutated. Strikingly, EpiC1 and EpiC2B preferentially inhibit tomato C14 rather than self-produced Pains, suggesting that they coevolved with Pains to avoid self-inhibition. To mimic the avoidance of inhibition by EpiCs, we engineered C14 (eC14) with seven Pain1 residues that potentially disturb the EpiCs–C14 interface. This eC14 is less sensitive to inhibition by EpiCs and enhances resistance to P. infestans infection. This strategy demonstrates that a pathogen-inspired protein engineering approach can increase crop resistance to plant pathogens.